Longitudinal study of ICET-A on glucose tolerance, insulin sensitivity and β-cell secretion in eleven β-thalassemia major patients with mild iron overload: Low serum ferritin and glucose homeostasis in β-thalassemia major - De Sanctis, Vincenzo; Soliman, Ashraf T; Daar, Shahina; Tzoulis, Ploutarchos; Di Maio, Salvatore; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2023)
Background: Iron chelation therapy (ICT) is the gold standard for treating patients with iron overload, though its long-term effects are still under evaluation. According to current recommendations regarding transfusion-dependent (TD) β-thalassemia major (β-TM) patients, their serum ferritin (SF) levels should be maintained below 1,000 ng/mL and ICT should be discontinued when the levels are <500 ng/mL in two successive tests. Alternatively, the dose of chelator could be considerably reduced to maintain a balance between iron input and output of frequent transfusions. Study design: Due to the paucity of information on long-term effects of ICT in β-TM with low SF levels on glucose homeostasis, the International Network of Clinicians for Endocrinopathies in Thalassemia and Adolescence Medicine (ICET-A) promoted a retrospective and an ongoing prospective observational study with the primary aim to address the long-term effects of ICT on glucose tolerance and metabolism (β-cell function and peripheral insulin sensitivity) in adult β-TM patients with persistent SF level below 800 ng/mL. Patients and Methods: 11 β-TM patients (mean age: 35.5 ± 5.5 years; SF range: 345-777 ng/mL) with normal glucose tolerance test (OGTT) or abnormal glucose tolerance (AGT) for a median of 5.3(1.1-8.3) years. Results: Abnormal glucose tolerance (AGT) was observed in 7 patients (63.6%) at first observation and ) persisted in 6 patients (54.5%) at last observation. None of them developed diabetes mellitus. AGT was reversed in two patients. One patient with NGT developed early glucose intolerance (1-h PG ≥155 and 2-h PG <140 mg/dL). Three out of 5 patients with isolated impaired glucose tolerance presented a variation of ATG. Stabilization of low indices for β-cell function and insulin sensitivity/resistance was observed. One patient developed hypogonadotrophic hypogonadism. Three out of 6 patients with SF below 500 ng/dL had hypercalciuria. Conclusion: Despite low SF level, the burden of endocrine complications remains a challenge in β-TM patients. The ability to keep iron at near "normal" level with acceptable risks of toxicity remains to be established.